How School Principals Navigate Leadership Challenges in Integrating Technology into the Teaching-Learning Process - K S P Sisindra; Nawastheen Fareed Mohamed (Postgraduate Program, University of Mataram, 2025)
This study aims to examine the challenges faced by school principals in Sri Lanka within diverse contexts when they attempt to integrate technology into the teaching learning process. A qualitative research design was used. Semi structured interviews were carried out with ten school principals in Sri Lankan schools within Sinhala, Tamil and English mediums across four Sri Lankan districts. Data were analyzed using thematic analysis. School principals play key roles such as facilitators and supporters of technology integration. However, many of them do not have a clear vision on technology integration. Initiatives such as STEM education were seen to be implemented. Limited resources, scarcity of infrastructure, teacher resistance and lack of awareness in policies related to technology integration are the main challenges faced by school principals. Disparities in urban/rural contexts and between schools teaching in different languages exacerbated these challenges. This study uncovers interesting insights into how Sri Lankan principals lead technology integration in the teaching-learning process. The study underscored specific challenges and effective recommendations to overcome these challenges to help principals integrate technology into the teaching-learning process, while improving the overall equity and quality of education.